Deepfakes and documentary practice in an age of misinformation. Issue 3 (4th May 2022) - Hight, Craig
ABSTRACT: The emergence of deepfakes is the latest form to prompt anxieties over the wider implications of misinformation. This chapter explores possibilities for how these technologies extend the repertoire of modalities available for documentary makers. While these 'synthetic media' offer a disruption of the documentary genre, they are also a continuation of long-standing trends within software culture and also clearly augment practices which are deeply embedded within the documentary genre. This discussion draws upon Wardle and Derakhshan's 'misinformation' and 'disinformation' framework to highlight the increasing complexity of documentary's forms and the challenges they pose to audiences. The limited experiments in integrating synthetic media into documentary media in a productive way suggest especially the possibilities for using these to develop more openly reflexive content. The proliferation of synthetic media forms prompt a wider need within documentary practitioners for critical data practices, software literacy, and ethical practices embedded within a broader understanding of automated, networked and entangled media systems. And they challenge documentary designers to strategise the nature of their content, and engage more directly with their audiences on questions around evidence, trust, authenticity and the nature of documentary media within an era of misinformation.